Socialization of the Use of Tiktok Shop to MSME Players in Rural Community to Improve the Performance of their MSMEs - Irfansyah, Irfansyah; Magisa , Nurul Septya; Nurmansyah , Andry; Yunan , Nadiya; Mahmuddin, Mahmuddin (Journal Of Human And Education (JAHE), 2024)
Abstract Keude Bieng Village, which is located on Jalan Meulaboh-Banda Aceh, precisely in Lhoknga District, Aceh Besar Regency, is a tourist area that is very popular with tourists. However, most of the residents along Lhoknga Road opened stalls for visiting tourists. They also produce various typical Acehnese foods and produce various rattan craft skills which are part of micro, small and medium enterprises (MSMEs). The rattan and other bamboo craftsmen who sell along the street of Keude Bieng create economic activity for the community. However, in this modern digital era, many MSMEs still find it difficult to use digital marketing media, so not many people use it. Based on these problems, digital marketing outreach and training, especially the TikTok Shop Application, was carried out for MSME business actors in Keude Bieng Village, Lhoknga District, Aceh Besar Regency. The choice of marketing media using TikTok is because TikTok is currently an application that is loved by the public and the benefits are felt and also its influence on purchasing a product marketed on the application with the aim that MSMEs who use the application can promote and sell products. The aim of carrying out this Community Service activity is to optimize marketing activities for MSMEs digitally so that MSME products in Keude Bieng Village, Lhoknga District, Aceh Besar Regency can cover a wider scope. Community Service Activities in Keude Bieng Village are carried out by holding outreach and training for all MSME players. Based on the activities that have been carried out, MSMEs who do not yet have a TikTok Shop account can be helped to manage the products produced on the platform and understand how to market them. The results of the community service program for MSMEs in Keude Bieng Village, Lhoknga District, Aceh Besar Regency, had a positive impact on those who took part. This is evidenced by increases in knowledge, skills and product quality, number, type and turnover, management capabilities, profits and the number of new entrepreneurs. Keyword : Tiktok Shop, MSMEs, Keude Bieng Village, Handicrafts